2018
DOI: 10.3390/molecules23020359
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Soluble and Insoluble-Bound Phenolics and Antioxidant Activity of Two Chinese Mistletoes

Abstract: Mistletoes are used medicinally in order to treat various human illnesses. Few studies have reported on the phenolic content and antioxidant properties of Chinese mistletoes (CMs). In this work, the total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities of soluble and insoluble-bound phenolic extracts from CMs hosted by Camellia assamica (Mast.) Chang (CMC) and Pyrus, i, f. (CMP) were compared. Phenolic compounds in CMC and CMP were identified and quantified using high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Phenolic compounds are a chemically diverse group of secondary metabolites that occur ubiquitously in plants [37]. They can be divided into several groups, including phenolic acids, flavonoids, stilbenes, and lignans, depending on their chemical structure [38]. They commonly act as chemical and physical barriers to protect plants against biotic and abiotic stress [39], provide protection against excess sunlight by absorbing high energy wavelengths [40], and they can also protect plants from various pests and diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are a chemically diverse group of secondary metabolites that occur ubiquitously in plants [37]. They can be divided into several groups, including phenolic acids, flavonoids, stilbenes, and lignans, depending on their chemical structure [38]. They commonly act as chemical and physical barriers to protect plants against biotic and abiotic stress [39], provide protection against excess sunlight by absorbing high energy wavelengths [40], and they can also protect plants from various pests and diseases [41].…”
Section: Discussionmentioning
confidence: 99%
“…The compositions of bound phenolic components in the SDF and IDF were analyzed according to a published method (Li et al., 2018). In brief, after the extract was filtered through a 0.45 µm filter, phenolic analysis was carried out using a high‐performance liquid chromatography system (1260 Infinity; Agilent Technologies, Waldbronn, Germany) connected to a diode array detector (G1315D DAD) and equipped with a reversed‐phase C18 column (250 mm*4.6 mm, 5 µm, YMC Pack, Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic compounds are health‐promoting phytochemicals in plants due to their well‐documented antioxidative, anti‐inflammatory, anticarcinogenic, antimutagenic, and antiviral activities (Devi, Vijayabharathi, Sathyabama, Malleshi, & Priyadarisini, 2014; Dueñas et al., 2016; Pozuelo et al., 2012; Villanueva‐Carvajal, Bernal‐Martínez, García‐Gasca, & Dominguez‐Lopez, 2013). Depending on their solubility characteristics, phenolic compounds occur in soluble and insoluble‐bound forms (Chandrasekara & Shahidi, 2010; Li et al., 2018). Soluble phenolic compounds are generally extracted by aqueous or aqueous‐organic solvent mixtures such as methanol–water or acetone–water (Acosta‐Estrada, Gutiérrez‐Uribe, & Serna‐Saldívar, 2014; Devi et al., 2014; Pellegrini et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…f.) has been identified as a rich source of DF and phenolic compounds as it is grown under harsh environments (Liang et al., 2017). Li et al., 2018) and Yang, Dang, & Fan, 2018 have reported that a large number of polyphenols with effective antioxidant activities were determined in different colored Tibetan hulless barley and cultivated Qinghai‐Tibet highland barley varieties. Our research team has reported that the contents of insoluble‐bound phenolics are 14.30 ± 0.04 and 5.90 ± 0.67 µmol ferulic acid equivalents (FAE)/g dry sample (DS) for IDF and SDF derived from hulless barley, respectively (Li et al., 2019).…”
Section: Introductionmentioning
confidence: 99%